2018
DOI: 10.3390/app8101868
|View full text |Cite
|
Sign up to set email alerts
|

Design of Wing Root Rotation Mechanism for Dragonfly-Inspired Micro Air Vehicle

Abstract: This paper proposes a wing root control mechanism inspired by the drag-based system of a dragonfly. The previous mechanisms for generating wing rotations have high controllability of the angle of attack, but the structures are either too complex or too simple, and the control of the angle of attack is insufficient. In order to overcome these disadvantages, a wing root control mechanism was designed to improve the control of the angle of attack by controlling the mean angle of attack in a passive rotation mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…As previously mentioned, a bumblebee wing shape is considered for the four wings. This selection is based on the studies carried out by Hassanalian et al [18,19] where seven different insect wings were studied and compared to determine the optimal wing shape for hovering and forward flight. For the hovering flight study, a quasi-steady theory is employed to determine the optimal wing shape for two cases, one considering all wings to have an equal wing surface and one with all wings having an equal wingspan [29].…”
Section: Wing Selection and Manufacturingmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously mentioned, a bumblebee wing shape is considered for the four wings. This selection is based on the studies carried out by Hassanalian et al [18,19] where seven different insect wings were studied and compared to determine the optimal wing shape for hovering and forward flight. For the hovering flight study, a quasi-steady theory is employed to determine the optimal wing shape for two cases, one considering all wings to have an equal wing surface and one with all wings having an equal wingspan [29].…”
Section: Wing Selection and Manufacturingmentioning
confidence: 99%
“…There is a large variety of actuation mechanisms used in the manufacturing of drones [10][11][12][13][14][15][16][17][18][19]. When selecting these mechanisms, many crucial factors must be considered and compared to select the appropriate actuator for the desired drone design.…”
Section: Actuation and Fuselage Section And Manufacturingmentioning
confidence: 99%
“…In order to study the mutual interaction between the rotors, various combinations with different spacing (1 d-2 d) and tilt angle (0-50 deg) are numerically simulated with ANSYS. The N-S equation model is applied to analyze the characteristics of the external flow field [29]. Also, mesh refinement is performed on four rotor regions with a large gradient of physical field flow.…”
Section: Computational-fluid-dynamics Analysismentioning
confidence: 99%
“…It uses a sliding mode observer to estimate the fault magnitude and location. Inspired by the flight mechanism of the insect dragonfly, a wing root control mechanism was introduced to the MAV (micro air vehicle) stabilizing hovering, by Jang and Yang [24]. It was shown that the mechanism can control the flight mode easily.…”
Section: Advanced Mobile Roboticsmentioning
confidence: 99%